Pengaruh Komitmen Organisasi Dan Konflik Kerja Terhadap Turnover Intention Pada Cv. Karya Surya Sejati - Surya Aji Zulmi; Achmad Agus Prioyono; Etty Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to analyze the effect of organizational commitment and work conflict on turnover intention simultaneously and partially in CV. Karya Surya Sejati.This study uses quantitative methods by collecting data through questionnaire. The population in this study were employees at CV. Karya Surya Sejati. The sampling technique used the census method. Example consisting of 54 respondents with questionnaire collection technology. That The data analysis method used in this study used descriptive analysis and multiple regression analysis.The results of this study indicate that organizational commitment and work conflict have a significant impact on turnover intention. research results can provide input to employees CV. Karya Surya Sejati especially organizational commitment and work conflict. Keywords: Organizational Commitment, Work Conflict, Turnover Intention.